2019
DOI: 10.1007/s13364-019-00440-7
|View full text |Cite
|
Sign up to set email alerts
|

Can landscape characteristics help explain the different trends of Cantabrian brown bear subpopulations?

Abstract: A central challenge in animal conservation is to understand how a population may respond to different habitat characteristics, which may affect their growth and viability. At the beginning of the 20 th century, the Cantabrian brown bear Ursus arctos population (north-western Spain) was separated into western and eastern subpopulations. Today, brown bears in the Cantabrian Mountains are recovering and the two subpopulations are reconnected. However, the western portion of the population represents ca. 90% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Brown bears have been continuously present in the eastern Cantabrian Mountains [ 29 ], and a recent habitat assessment has shown that habitat characteristics are similar in both Cantabrian subpopulations [ 30 ]. Under these circumstances, the removal of individuals will produce an attractive sink [ 15 ], as has been specifically suggested for this bear population [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown bears have been continuously present in the eastern Cantabrian Mountains [ 29 ], and a recent habitat assessment has shown that habitat characteristics are similar in both Cantabrian subpopulations [ 30 ]. Under these circumstances, the removal of individuals will produce an attractive sink [ 15 ], as has been specifically suggested for this bear population [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the human footprint (i.e. landscape variables associated with humans) of the habitat is also higher in the western subpopulation [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one, between France and Spain, has been reinforced by translocations of bears from Slovenia since 1996 due to its critical and imminent risk of extinction (Gonzalez et al, 2016; Quenette et al ., 2001; Swenson et al ., 2011). The other bear population inhabits the Cantabrian Mountains, where two subpopulations are recovering and recently interconnected after a long isolation (Gonzalez et al, 2016; Lamamy et al ., 2019; Zarzo‐Arias et al ., 2019). Within their range, bears coexist with several human activities, which may be attractive to them.…”
Section: Introductionmentioning
confidence: 99%
“…The value of the cell neighborhood parameter was specified in eight different papers: seven chose a Moore definition [13][14][15][16][17][18][19][20] and one a von Neumann definition [21]. The 16 papers which exclusively employed LecoS [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] used an 8-cells neighborhood rule, as it is the only setting available in the add-on; a similar hypothesis is applicable to the four works which used r.li in GRASS [38][39][40][41], which uses a 4-cells neighborhood definition. The papers which did not specify the definition of the neighborhood in FRAGSTATS are assumed to have used a 8-cells definition, since this is the default setting [42], although it is not possible to prove this assumption.…”
Section: Literature Reviewmentioning
confidence: 99%